Leaping to virtual community: motivational behaviours for bloggers / Noorazura Durani, Wan Azfarozza Wan Athmar and Shahril Anuar Abdul Ghalim - Durani, Noorazura; Wan Athmar, Wan Azfarozza; Abdul Ghalim, Shahril Anuar (Faculty of Administrative Science and Policy Studies, 2012)
People nowadays roam in the new realm as we know it today as cyberspace. The intersection of humanity and technology has created a new world known as virtual community. Most of us today exist using platforms without meeting face to face and yet able to exchange words and ideas. Blog is one type of virtual community which is growing in its popularity day by day. People who roam in the realm of blogs known as bloggers express or share their feelings, emotions, experience and information. The catalysts that drive this community to grow rapidly are based on two types of motivations which are intrinsic motivation and extrinsic motivation. The intrinsic motivation is the process of performing interesting activities and experience that bloggers find enjoyable and satisfying. Whereas, extrinsic motivation for bloggers focuses on the external rewards whereby the readers and external bodies of social media give recognition to the successfulness of each blog existed in the cyberspace. In the context of Malaysia’s blogging culture, people started taking notice of the impact of blogs during the 2008 general election when youth voters were being said to be influenced largely by the views and opinions posted in the political blogs. The blogging trend later transcends into other genre such as entertainment, fashion, business and charity. The existence of these various genres is explained through The Users and Gratification Theory which proposed that individual needs and motivations are the driving force behind people’s interaction with media. Hence, this conceptual paper explores the ever changing social media landscape, phenomenon and possibilities that could shape virtual communities and bloggers motivation behaviours.